Physiologic and behavioral indicators of energy deficiency in female adolescent runners with elevated bone turnover - Barrack, M. T.; Van Loan, M. D.; Rauh, M. J.; Nichols, J. F. (The American Journal of Clinical Nutrition, 2010)
Female adolescent runners have an elevated prevalence of low bone mass for agemdashan outcome that may be partially due to inadequate energy intake.